Microwave Absorption Properties of Double-Layer RADAR Absorbing Materials Based on Doped Barium Hexaferrite/TiO2/Conducting Carbon Black - Sukanta Das; G. C. Nayak; S. K. Sahu; P. C. Routray; A. K. Roy; H. Baskey (Journal of Engineering, 2014)
In this report, we demonstrate microwave absorption properties of barium hexaferrite, doped barium hexaferrite, titanium dioxide and conducting carbon black based RADAR absorbing material for stealth application. Double-layer absorbers are prepared with a top layer consisting of 30% hexaferrite and 10% titanium dioxide while the bottom layer composed of 30% hexaferrite and 10% conducting carbon black, embedded in chloroprene matrix. The top and bottom layers are prepared as impedance matching layer and conducting layer, respectively, with a total thickness of 2 mm. Microwave absorption properties of all the composites were analyzed in X-band region. Maximum reflection loss of −32 dB at 10.64 GHz was observed for barium hexaferrite based double-layer absorber whereas for doped barium hexaferrite based absorber the reflection loss was found to be −29.56 dB at 11.7 GHz. A consistence reflection loss value (>−24 dB) was observed for doped barium hexaferrite based RADAR absorbing materials within the entire bandwidth.